A simplified computational model for seismic performance evaluation of steel plate shear wall-frame structural systems. (October 2021) - Bai, Jiulin; Zhang, Jianyuan; Jin, Shuangshuang; Wang, Yu-hang
Abstract: The steel plate shear wall (SPSW)-frame structure is a high-performance lateral force-resisting system, which has been widely utilized in high-rise buildings, especially in seismic-prone regions. The complexity of SPSW modeling and the interaction between SPSWs and frame, make it very time-consuming and low-efficiency for the performance-based seismic performance evaluation of SPSW-frame systems. This paper developed a simplified computational analytical model of SPSW-frame system based on the lateral deformation characteristics of the system. The simplified flexure-shear (F-S) model was composed of the flexure springs and shear springs, to respectively simulate the behaviors of SPSW and frame. Also, the P -delta column was incorporated into the simplified model to account for the P -delta effect. The material parameters of the flexure spring and shear spring were calibrated by the response spectrum method. By employing the PEER full probability theory, the seismic performance evaluation of two 7- and 15-story SPSW-frame structures were carried out using the simplified F-S model and refined finite element method (FEM). The analytical results demonstrated that the simplified flexure-shear model can achieve nearly the same performance parameters, compared with the refined FEM. Furthermore, the repair cost and repair time of the SPSW-frame structures mainly came from the non-structural components.